Peran Adnan Kapau Gani dalam Perjuangan Militer Daerah Sumatera Selatan Tahun 1945-1949 - Berlian Susetyo; Priyanti Gani; Muhammad Wahayuni (Historia Madania: Jurnal Ilmu Sejarah, 2022)
The independence achieved by the Indonesian people had to go through the twists and turns of the struggle to sacrifice property, soul and body due to the colonial nation that once controlled Indonesia, came to colonize again, namely the Dutch. So that in this struggle to defend Indonesia's independence, heroes emerged who wanted to always fight to defend the sovereignty of the Indonesian nation from Dutch influence. Adnan Kapau Gani is a perfect fighter who understands political and military issues. His thoughts in the military sector have inspired and contributed greatly to the struggle of the Indonesian people. This study aims to reveal the role of Adnan Kapau Gani in the military struggle of the South Sumatra region. The research method used is the historical method, with stages: heuristics, source criticism, interpretation, and historiography. The results showed that Adnan Kapau Gani had a big role in the formation of TKR Sumatra by being the organizer/coordinator which he did in Palembang. With the military already formed, Adnan Kapau Gani convinced the central government that in terms of defense it was necessary to reorganize the Sumatran TRI, so the South Sumatra Sub-Commandment (SUBKOSS) was formed and he himself served as commander in chief, as well as Deputy Minister of Defense. Then in the Second Dutch Aggression, Adnan Kapau Gani was appointed military governor of the special region of South Sumatra to lead a guerrilla war by organizing the people and fighters against the Dutch troops. So he earned the title of great guerrilla leader.